Method for manufacturing copper aluminum clad material, method for manufacturing heat sink, copper aluminum clad material and heat sink
By forging copper and aluminum members with a coating layer to suppress oxide formation and enhance adhesion, the method addresses the challenges of joint integrity and mass production in copper-aluminum clad materials for heat sinks.
Patent Information
- Application Number
- JP2023117591
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2025-01-30
AI Technical Summary
Existing methods for manufacturing copper-aluminum clad materials for heat sinks face issues such as oxide formation at the joint surfaces, leading to reduced adhesion and peeling, and are not suitable for easy mass production.
A method involving forging and joining copper and aluminum members with a coating layer to suppress oxide formation, using metal materials like titanium, vanadium, and nickel, and applying plating processes to ensure close contact and diffusion bonding.
The method enables the production of copper-aluminum clad materials with improved adhesion and ease of manufacturing, reducing oxide formation and facilitating mass production without the need for large-scale equipment.
Smart Images

Figure 2025014773000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for manufacturing a copper-aluminum clad material, a method for manufacturing a heat sink, a copper-aluminum clad material, and a heat sink. [Background technology]
[0002] Heat sinks are used to dissipate heat from electronic components. Copper or aluminum is used as the material for heat sinks. Copper has excellent thermal conductivity and solder wettability. Aluminum has excellent cost, light weight, corrosion resistance, and workability. In order to utilize the properties of both copper and aluminum, development of a heat sink is underway in which copper is provided on the side where electronic components are placed and aluminum is provided on the other side where fins are formed.
[0003] Patent Document 1 discloses a heat sink that is a composite plate (clad material) made of aluminum and copper, in which heat dissipation fins made of aluminum are provided on the surface of the aluminum plate of the composite plate, and the rolled surface of the composite plate is metallurgically bonded (diffusion bonded). Patent Document 1 describes that the aluminum plate and the copper plate are heated separately, and then the two are stacked and rolled to metallurgically bond the composite plate. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 9-298259 Summary of the Invention [Problem to be solved by the invention]
[0005] In Patent Document 1, a composite plate made of a copper member and an aluminum member is hot-rolled, so there is a risk of oxides being generated at the bonding surface between the copper member and the aluminum member. In the area where oxides are generated, poor bonding occurs between the copper member and the aluminum member, which leads to a problem of reduced adhesion of the clad material and peeling. In addition, from the viewpoint of mass production, it is desired to be able to easily manufacture a clad material or a heat sink using a clad material.
[0006] From this viewpoint, an object of the present invention is to provide a method for manufacturing a copper-aluminum clad material that is easy to manufacture and does not easily peel off, a method for manufacturing a heat sink, and a copper-aluminum clad material and a heat sink. [Means for solving the problem]
[0007] [1] In order to solve the above problems, the present invention provides a method for producing a copper-aluminum clad material by forging and joining a copper member made of copper or a copper alloy and an aluminum member made of aluminum or an aluminum alloy, the copper member having a coating layer formed of a metal material in close contact with the aluminum member on a surface facing the aluminum member, the coating layer suppressing the generation of oxides, and the method includes a lamination process for laminating the copper member and the aluminum member to form a laminate with the coating layer and the aluminum member facing each other, and a forging process for forging and joining the laminate by hot forging, characterized in that in the forging process, with the copper member and the coating layer in close contact with each other, a new surface of the coating layer and a new surface of the aluminum member are closely contacted and joined.
[0008] [2] In the method for producing a copper-aluminum clad material according to [1], in the forging step, the coating layer is divided to form a divided portion between the divided coating layers where the coating layer is not present, and the aluminum member is introduced into the divided portion, thereby bringing a new surface of the copper member exposed at the divided portion into close contact with a new surface of the aluminum member, thereby joining the copper member and the aluminum member.
[0009] [3] In the method for producing a copper-aluminum clad material according to [1] or [2], it is preferable that the metal material is at least one metal selected from the group consisting of titanium, vanadium, chromium, manganese, cobalt, nickel, molybdenum, rhodium, palladium, silver, platinum, and gold, or an alloy thereof.
[0010] [4] The method for producing a copper-aluminum clad material according to any one of [1] to [3] above preferably further comprises a coating step of forming the coating layer on the copper member.
[0011] [5] It is preferable in the method for producing a copper-aluminum clad material according to any one of [1] to [4], that the coating layer is a plating layer, and in the coating step, the plating layer is formed by subjecting the copper member to a plating treatment.
[0012] [6] In the method for producing a copper-aluminum clad material according to [5], the plating treatment is preferably Ni electric plating, electroless Ni-P plating, or Ni-Cr electric plating.
[0013] [7] The method for producing a copper-aluminum clad material according to [5] or [6] is preferably such that the thickness of the plating layer is 15 μm or less.
[0014] [8] The method for producing a copper aluminum clad material according to any one of [1] to [7] above is preferably further provided with a heating step of preheating the laminate in an air atmosphere, and in the forging step, the laminate preheated in the heating step is hot forged in an air atmosphere.
[0015] [9] The present invention is a method for manufacturing a heat sink, which includes forming fins on an aluminum member while carrying out a method for manufacturing a copper aluminum clad material according to any one of [1] to [8], and is characterized in that in the forging process, the laminate is forged and joined by hot forging, and fins are formed on the aluminum member.
[0016]
[10] The present invention is characterized in that it is a method for manufacturing a heat sink, comprising a cutting fin formation process for forming fins by performing a cutting process on the aluminum member after carrying out the method for manufacturing a copper aluminum clad material described in any one of [1] to [8].
[0017]
[11] The present invention relates to a copper-aluminum clad material in which a copper member made of copper or a copper alloy and an aluminum member made of aluminum or an aluminum alloy are joined together, the copper member and the aluminum member are joined together through an intervening layer made of a metal material, the copper member and the intervening layer are in close contact with each other, and the intervening layer and the aluminum member are in close contact with each other and joined together, and the intervening layer has a thickness of 10 μm or less.
[0018]
[12] It is preferable that the intermediate layer has a continuous portion where the intermediate layer is present and a divided portion where the intermediate layer is not present, one surface of the continuous portion is closely joined to the copper member and the other surface of the continuous portion is closely joined to the aluminum member, and at the divided portion, the copper member exposed from the intermediate layer and the aluminum member are closely joined to each other in the copper aluminum clad material described in
[11] .
[0019]
[13] The metal material is preferably a copper aluminum clad material according to
[11] or
[12] , which contains nickel.
[0020]
[14] The present invention relates to a heat sink in a copper-aluminum clad material in which a copper member made of copper or a copper alloy and an aluminum member made of aluminum or an aluminum alloy are bonded together, the heat sink having fins formed on the aluminum member, the copper member and the aluminum member are bonded together with an intervening layer made of a metal material, the copper member and the intervening layer are in close contact with each other, and the intervening layer and the aluminum member are in close contact with each other, and the intervening layer has a thickness of 10 μm or less. Effect of the Invention
[0021] According to the present invention, it is possible to obtain a manufacturing method of a copper-aluminum clad material, a manufacturing method of a heat sink, and a copper-aluminum clad material and a heat sink that are easy to manufacture and difficult to peel off. [Brief description of the drawings]
[0022] [Figure 1] FIG. 1 is a side view of a copper aluminum clad material according to a first embodiment of the present invention. [Diagram 2] FIG. 2 is a side view showing a preparation step and a covering step of the method for producing a copper aluminum clad material according to the first embodiment. [Diagram 3] 3 is a side view showing a lamination step and a heating step of the manufacturing method of the copper aluminum clad material according to the first embodiment. FIG. [Figure 4] FIG. 2 is a side view showing a forging step of the method for producing a copper aluminum clad material according to the first embodiment. [Diagram 5] FIG. 4 is a side view of a heat sink according to a second embodiment of the present invention. [Figure 6] FIG. 4 is a side view of a copper aluminum clad material according to a third embodiment of the present invention. [Figure 7] FIG. 7 is an enlarged view of FIG. [Figure 8] FIG. 11 is a side view showing a forging step of a method for producing a copper aluminum clad material according to a third embodiment. [Figure 9]FIG. 11 is a side view of a heat sink according to a fourth embodiment of the present invention. [Figure 10] 1 is a table showing test conditions and test results of Test 1. [Figure 11] 1 is a scanning electron microscope photograph of Example 1. [Figure 12] 1 is a scanning electron microscope photograph of Example 2. [Figure 13] 1 is a scanning electron microscope photograph of Example 3. [Figure 14] 1 is a scanning electron microscope photograph of Comparative Example 1. [Figure 15] FIG. 14 is an enlarged photograph. [Figure 16] 1 is a scanning electron microscope photograph of Example 4. [Figure 17] 1 is a scanning electron microscope photograph of Example 5. [Figure 18] 1 is a scanning electron microscope photograph of Example 6. [Figure 19] 1 is a scanning electron microscope photograph of Example 7. [Figure 20] 1 is a scanning electron microscope photograph of Comparative Example 2. [Figure 21] This is an enlarged photograph of FIG. [Figure 22] 1 is a scanning electron microscope photograph of Example 8. [Diagram 23] 1 is a scanning electron microscope photograph of Comparative Example 3. [Figure 24] FIG. 24 is an enlarged view of FIG. [Diagram 25] 1 is a scanning electron microscope photograph of Comparative Example 4. [Figure 26] FIG. 25 is an enlarged view of FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] The embodiments of the present invention will be described with reference to the drawings as appropriate. The present invention is not limited to the following embodiments. The components in the embodiments and modifications can be combined in part or in whole as appropriate. The directions in the description are used for convenience and do not limit the present invention. In addition, for the convenience of explanation, the intermediate layer (coating layer) is depicted in a schematic diagram with the actual scale of the member changed.
[0024] [1. First embodiment] [1-1. Copper-aluminum clad material] A copper aluminum clad material according to the first embodiment of the present invention will be described. As shown in Fig. 1, a copper aluminum clad material 1 according to this embodiment includes a copper member 2, an aluminum member 3, and an intermediate layer 4. The copper aluminum clad material 1 is in the form of a plate, and is a member in which the copper member 2 and the aluminum member 3 are bonded together.
[0025] The copper member 2 is made of copper or a copper alloy and has a plate shape. The copper member 2 may be of any material that can be forged. For example, oxygen-free copper (C1020) having a copper purity of 99.0% or more, tough pitch copper (C1100), etc., may be used as the copper member. In addition, it is preferable that the content of components other than copper is 0.1 mass % or less. This can increase the strength and workability of the copper member. In addition, it is preferable that the copper member is a 1000 series. This can increase the electrical conductivity and thermal conductivity of the copper member. This is particularly suitable when the copper aluminum clad material is used as a heat sink.
[0026] The aluminum member 3 is made of aluminum or an aluminum alloy and has a plate shape. The aluminum member 3 may be of any material that can be forged, and the composition of the aluminum member may be appropriately set. For example, 1000 series pure aluminum, 2000 series, 6000 series, or 7000 series aluminum alloys, or age-hardened alloys thereof may be used as the aluminum member 3. In addition, the aluminum member 3 preferably contains, for example, 2 mass% or less of components other than aluminum. This can improve the strength, corrosion resistance, and workability (machinability, rollability) of the aluminum member. In addition, the aluminum member preferably contains, for example, 0.1 mass% or less of manganese. This can improve the thermal conductivity of the aluminum member. In addition, the aluminum member is preferably a 6000 series alloy. This can improve the strength and corrosion resistance of the aluminum member.
[0027] The intermediate layer 4 is a portion formed in a layer shape between the copper member 2 and the aluminum member 3. In this embodiment, the intermediate layer 4 is formed over the entire surface of the copper member 2, but it is sufficient that the intermediate layer 4 is formed at least between the copper member 2 and the aluminum member 3.
[0028] The intermediate layer 4 is made of a metal material, and is, for example, at least one metal selected from the group consisting of titanium, vanadium, chromium, manganese, cobalt, nickel, molybdenum, rhodium, palladium, silver, platinum, and gold, or an alloy thereof. The thickness of the intermediate layer 4 may be appropriately set, and is, for example, 10 μm or less, preferably 9 μm or less, more preferably 8 μm or less, further preferably 7 μm or less, and particularly preferably 5 μm or less. Whether the intermediate layer 4 is made of a desired metal material can be determined by observing the joint cross section where the intermediate layer 4 exists using energy dispersive X-ray spectroscopy (SEM-EDS: Energy Dispersive X-ray Spectroscopy) or electron probe micro analyzer (EPMA) and performing a composition analysis of the region of the intermediate layer 4.
[0029] The intermediate layer 4 can be formed, for example, by subjecting the copper member 2 to a plating process, but may be formed by other methods. When the intermediate layer 4 is formed by a plating process, Ni electric plating, electroless Ni-P plating, Ni-Cr electric plating, or the like can be performed.
[0030] There is no oxide film between the copper member 2 and the intermediate layer 4, and they are joined in an intimate contact state. Moreover, there is no oxide film between the intermediate layer 4 and the aluminum member 3, and they are joined in an intimate contact state. More specifically, a new surface formed by breaking the oxide film of the intermediate layer 4 and a new surface formed by breaking the oxide film of the aluminum member 3 are joined in an intimate contact state by hot forging. The significance of this intimate contact will be described later.
[0031] [1-2. Manufacturing method of copper-aluminum clad material] Next, a method for producing a copper-aluminum clad material according to the present embodiment will be described. In the method for producing a copper-aluminum clad material according to the present embodiment, a preparation step, a covering step, a lamination step, a heating step, and a forging step are performed in this order.
[0032] The preparation step is a step of preparing a copper member 2 and an aluminum member 3, as shown in Fig. 2. The coating step is a step of forming a coating layer 10 on an opposing surface 2a of the copper member 2 that faces the aluminum member 3, as shown in Fig. 2. The coating layer 10 may be provided on at least the opposing surface 2a, but in this embodiment, the coating layer 10 is formed on the entire surface of the copper member 2.
[0033] The coating process is not limited to a coating method, but is performed by plating in this embodiment. For example, electric Ni plating, electroless Ni-P plating, or electric Ni-Cr plating can be used as the plating process. In the coating process, it is preferable to remove the oxide film between the copper member 2 and the coating layer 10 and bond them in a tightly adhered state, so that oxide is unlikely to be generated on the outer surface of the coating layer 10 when the forging process described later is performed.
[0034] The thickness of the plating layer in the coating step (thickness of the coating layer 10) may be appropriately set according to the material, film thickness, and forming conditions of the coating layer 10; the temperature of the preheating; and the pressure in the forging step. For example, the thickness of the plating layer is preferably 15 μm or less, more preferably 13 μm or less, and even more preferably 10 μm or less. By setting the thickness of the plating layer to 15 μm or less, the coating layer 10 deforms following the deformation of the copper member 2 and the aluminum member 3 during the forging step described later, so that it is possible to prevent the occurrence of voids between the copper member 2 and the coating layer 10, and between the aluminum member 3 and the coating layer 10.
[0035] In the lamination step, as shown in FIG. 3, the copper member 2 and the aluminum member 3 are laminated together in a state in which the coating layer 10 and the aluminum member 3 face each other to form a laminate 20.
[0036] The heating step is a step of preheating the laminate 20 as shown in FIG. 3. In the heating step, the laminate 20 is placed in a heating furnace (not shown) and preheated at a predetermined temperature. The heating step may be performed under an inert gas atmosphere such as argon gas or nitrogen gas, but in this embodiment, the preheating is performed in the air (in the air atmosphere). The predetermined temperature T is preferably a temperature at which, when a forging step described later is performed, the coating layer 10 is not divided, the oxide film (not shown) of the coating layer 10 is broken to expose the new surface 10a (see FIG. 4), and the oxide film (not shown) of the aluminum member 3 is broken to expose the new surface 3a (see FIG. 4). The predetermined temperature T can be set according to the solidus temperature of the aluminum member 3. For example, the predetermined temperature T is preferably solidus temperature × 50% (°C) ≦ T, more preferably solidus temperature × 65% (°C) ≦ T, even more preferably solidus temperature × 75% (°C) ≦ T, preferably T ≦ solidus temperature × 98% (°C), more preferably T ≦ solidus temperature × 93% (°C), and even more preferably T ≦ solidus temperature × 90% (°C).
[0037] As shown in FIG. 4, the forging process is a process in which the copper member 2 and the aluminum member 3 are pressed in a direction in which they approach each other with a predetermined pressure P to perform hot forging in the air (under the air atmosphere). In addition, the forging process is performed at room temperature. That is, in this embodiment, hot forging is performed in the air and at room temperature. The pressing time in the forging process may be set appropriately, but may be about 1 to 3 seconds, and is set to 1 second in this embodiment. The predetermined pressure P is preferably a pressure at which, when a forging process described later is performed, the coating layer 10 is not divided, and the oxide film (not shown) of the coating layer 10 is broken to expose the new surface 10a and the oxide film (not shown) of the aluminum member 3 is broken to expose the new surface 3a. In the forging process, the new surface 10a of the coating layer 10 exposed by breaking the oxide film is in close contact with the new surface 3a of the aluminum member 3, and is metal-bonded (diffusion bonded).
[0038] The pressure P in the forging process may be appropriately set according to the materials of the copper member 2 and the aluminum member 3 to be forged; the material, film thickness, and forming conditions of the coating layer 10; the temperature of preheating, etc., such that the copper member 2 and the coating layer 10 can be in close contact with each other and bonded to the new surface 10a of the coating layer 10 and the new surface 3a of the aluminum member 3. For example, the predetermined pressure P is preferably 200 (MPa) ≦ P, more preferably 300 (MPa) ≦ P, even more preferably 400 (MPa) ≦ P, and particularly preferably 500 (MPa) ≦ P. The upper limit of the predetermined pressure P is not particularly limited, but from the viewpoint of avoiding an increase in the size of the press machine and an increase in the equipment cost of the press machine, it is preferably P ≦ 1000 (MPa).
[0039] The meaning of "adhesion" in the claims "in the forging process, the copper member and the coating layer are in close contact with each other, and the new surface of the coating layer and the new surface of the aluminum member are in close contact with each other", "the copper member and the intermediate layer are in close contact with each other, and the intermediate layer and the aluminum member are in close contact with each other", and "one surface of the continuous portion and the copper member are in close contact with each other, and the other surface of the continuous portion and the aluminum member are in close contact with each other" will be explained. The "adhesion" here is defined as the porosity of the bonding interface being less than 15% when a scanning electron microscope photograph of a cross section at each interface (bonding interface) of the copper aluminum clad material 1 after the forging process is observed at a magnification of 1000 times. In other words, if the copper member 2 and the intermediate layer 4 are in close contact with each other at the interface after bonding, it can be determined that the copper member 2 and the coating layer 10 were bonded in a close contact state in the forging process. Furthermore, when the aluminum member 3 and the intermediate layer 4 are in close contact at the interface after joining, it can be determined that the newly formed surface of the coating layer 10 and the aluminum member 3 were joined in a tight contact state in the forging process. When the copper member 2 and the aluminum member 3 are in close contact at the interface after joining, it can be determined that the newly formed surface of the copper member 2 and the newly formed surface of the aluminum member 3 were joined in a tight contact state in the forging process.
[0040] The porosity refers to the ratio of the length of the region where voids exist to the length of the bonded interface in the interface direction in the bonded interface included in the field of view. In particular, the porosity refers to the ratio of the length of the region where voids exist to the length of the continuous part of the coating layer (intervening layer) in the interface direction of the bonded interface. For example, FIG. 23 shows Comparative Example 3 described later, and the scanning electron microscope was set to 1000 times, and the porosity (the ratio of the total length of voids to the total length of the continuous part in the bonded interface included in the field of view of the photograph) at the interface between the copper member 302 and the continuous part 305 of the coating layer (intervening layer 304) was about 26%, so it was determined that there was no adhesion (the bonding result was "bad").
[0041] The copper aluminum clad material 1 is formed by the above steps. In the forging step, the coating layer 10 is pressed and deformed (slightly thinner) to become the intermediate layer 4. At this time, the metallic material contained in the coating layer 10 may react with the aluminum of the aluminum member 3 to form an intermetallic compound. For example, when the coating layer 10 is a nickel layer made of nickel, the nickel reacts with the aluminum to generate an Al / Ni compound as an intermetallic compound. In this case, the intermediate layer 4 has a multi-layer structure having a metallic material layer made of a metallic material on the copper member 2 side and an intermetallic compound layer made of an intermetallic compound on the aluminum member 3 side. As a result, in the copper aluminum clad material 1, the copper member 2 and the metallic material layer of the intermediate layer 4 are in close contact with each other, and the intermetallic compound layer of the intermediate layer 4 and the aluminum member 3 are in close contact with each other and joined together.
[0042] The manufacturing method of the copper aluminum clad material is not limited to the above-mentioned embodiment, and for example, hot forging may be performed while heating the laminate 20 during the forging step without preheating. Also, the coating step may be omitted, and a copper member on which a coating layer has been formed in advance may be used.
[0043] [1-3. Effects] Generally, when forming a copper-aluminum clad material using a copper member and an aluminum member, hot forging is preferable to cold forging because it promotes metal bonding (diffusion bonding). However, when the copper member is heated, the oxide film of the copper member is oxidized and a large amount of oxide is generated on the surface of the copper member, making it practically difficult to bond the copper member and the aluminum member.
[0044] On the other hand, in the past, when forming a clad material of a copper member and an aluminum member, hot forging has been performed with a metal member interposed (simply arranged) between the two. However, if a metal member is simply interposed during hot forging, the linear expansion coefficients of each member are different, so the interposed metal member cannot follow the deformation of the copper member and the aluminum member during hot forging. This causes gaps between the copper member and the metal member, and between the aluminum member and the metal member, resulting in a decrease in thermal conductivity, a decrease in strength, etc. In addition, if a metal member is simply interposed during hot forging, the presence of an oxide film between the copper member and the metal member causes poor joining.
[0045] In addition, when a clad material of a copper member and an aluminum member is manufactured by hot forging, in order to avoid the influence of an oxide film formed on the surface of the copper member on the bonding, preheating and hot forging are performed in an inert gas atmosphere, and the surface oxide film is removed. In this case, large-scale devices and facilities are required to perform preheating and hot forging in an inert gas atmosphere and to remove the surface oxide film.
[0046] In this regard, according to the copper aluminum clad material 1 and the manufacturing method of the copper aluminum clad material according to the present embodiment, the coating layer 10 that suppresses the generation of oxides is provided on the copper member 2, and in the forging process, the newly formed surface 10a of the coating layer 10 and the newly formed surface 3a of the aluminum member 3 are bonded in close contact with each other while the copper member 2 and the coating layer 10 are in close contact with each other. More specifically, in the forging process, the heated copper member 2 and the aluminum member 3 are pressed against each other, whereby the oxide film of the coating layer 10 and the oxide film of the aluminum member 3 are destroyed, and the exposed newly formed surfaces 10a, 3a are bonded to each other. This makes it possible to perform bonding while suppressing the generation of oxides between the copper member 2 and the coating layer 10, and between the aluminum member 3 and the coating layer 10, and to form a copper aluminum clad material 1 that is difficult to peel off.
[0047] In addition, in this embodiment, since forging is performed in a state in which the copper member 2 and the coating layer 10 are in close contact with each other and the aluminum member 3 and the coating layer 10 are in close contact with each other, the coating layer 10 follows the deformation of the copper member 2 and the aluminum member 3 during forging. This makes it possible to suppress the generation of voids between the copper member 2 and the coating layer 10 and between the aluminum member 3 and the coating layer 10, and to form a copper-aluminum clad material 1 that is difficult to peel off. Furthermore, since the copper member 2 provided with the coating layer 10 is simply laminated with the aluminum member 3 and hot forged, no large-scale device or facility is required, and the copper-aluminum clad material 1 can be easily manufactured, thereby improving mass productivity.
[0048] In this embodiment, the metal material in the coating process is at least one metal selected from the group consisting of titanium, vanadium, chromium, manganese, cobalt, nickel, molybdenum, rhodium, palladium, silver, platinum, and gold, or an alloy thereof. When the coating layer 10 is formed from these materials, it is possible to suppress the generation of oxides on the copper member 2, and therefore it is possible to form a copper-aluminum clad material 1 that is more difficult to peel off. It is also possible to reduce the amount of oxide film generated on the surface of the coating layer 10. In particular, it is preferable to use nickel as the metal material for the coating layer 10 because of its high corrosion resistance and heat resistance.
[0049] Moreover, this embodiment includes a coating step of forming the coating layer 10 on the copper member 2. This makes it possible to easily form the coating layer 10.
[0050] In the present embodiment, the coating layer 10 in the coating step is a plated layer, and in the coating step, the plated layer is formed by plating the copper member 2. This makes it possible to easily form the coating layer 10. Furthermore, by plating, the oxide film of the copper member 2 is removed, and the copper member 2 and the coating layer 10 (plated layer) can be bonded in close contact with each other.
[0051] In the present embodiment, the plating is Ni electric plating, electroless Ni-P plating, or Ni-Cr electric plating. This allows the plating to be easily performed. In addition, such nickel-containing plating has excellent heat resistance, so that the coating layer 10 can be prevented from melting during the heating process. In addition, such nickel-containing plating can form the coating layer 10 that has excellent corrosion resistance and appropriate hardness and flexibility. This allows the coating layer 10 to follow the deformation of the copper member 2 and the aluminum member 3 during the forging process, so that the formation of voids at the interface (joint interface) can be suppressed.
[0052] In this embodiment, the thickness of the coating layer 10 (plating layer) is 15 μm or less. In the copper-aluminum clad material 1 according to this embodiment, the thickness of the intermediate layer 4 is 10 μm or less. As a result, during the forging process, the coating layer 10 also deforms in accordance with the deformation of the copper member 2 and the aluminum member 3, so that it is possible to suppress the generation of voids between the copper member 2 and the coating layer 10, and between the aluminum member 3 and the coating layer 10.
[0053] In addition, in this embodiment, after preheating in an air atmosphere, hot forging is performed in the air atmosphere in the forging process. Since the copper member 2 is provided with the coating layer 10, it is possible to prevent a brittle and thick oxide film from being formed on the surface of the copper member 2 when preheating is performed. Therefore, it is possible to prevent the oxide film formed on the surface of the copper member when preheating is performed from hindering the joining of the copper member 2 and the aluminum member 3. This makes it unnecessary to use a large-scale device for preheating and hot forging in an inert gas atmosphere for the purpose of preventing the formation of an oxide film on the surface of the copper member 2. Therefore, since there is no need to control the atmosphere when performing the forging process and hot forging can be performed in the air, it is possible to reduce manufacturing costs and easily manufacture the product, thereby improving mass productivity. In addition, since the forging process is completed in one second in this embodiment, it is also excellent in mass productivity.
[0054] For example, in this embodiment, the coating layer 10 is provided only on the copper member 2, but the coating layer 10 may also be provided on the aluminum member 3. Even in this embodiment, substantially the same effects as those of the above-mentioned embodiment can be obtained.
[0055] [2. Second embodiment] [2-1.Heat sink] Next, a heat sink and a manufacturing method of a heat sink according to a second embodiment will be described. As shown in Fig. 5, a heat sink 30 according to this embodiment includes a copper member 2, an aluminum member 3A, and an intermediate layer 4. The copper member 2 and the intermediate layer 4 are the same as those in the first embodiment.
[0056] The aluminum member 3A includes a base 31 and a plurality of fins 32. The base 31 is a plate-shaped portion and is joined to the copper member 2 via an intervening layer 4. The plurality of fins 32 are provided upright on the base 31 with gaps therebetween and are integrally formed with the base 31. There are no particular limitations on the method for forming the plurality of fins 32, and they can be formed, for example, by cutting.
[0057] [2-2. Heat sink manufacturing method] In the method for manufacturing a heat sink according to this embodiment, a preparation step, a covering step, a lamination step, a heating step, a forging step, and a fin forming step are performed in this order. The preparation step, covering step, lamination step, heating step, and forging step of the method for manufacturing a heat sink are the same as those of the method for manufacturing a copper aluminum clad material according to the first embodiment. In this embodiment, a cutting fin forming step in which fins are formed by cutting is performed as the fin forming step.
[0058] The cut fin forming process is a process in which a cutting process is performed on the aluminum member 3A of the copper-aluminum clad material to form a plurality of fins 32. In the cut fin forming process, for example, the plurality of fins 32 can be formed by cutting using a multi-cutter having a plurality of cutting teeth arranged in parallel.
[0059] [2-3. Effects] According to the heat sink and the manufacturing method of the heat sink according to the present embodiment described above, it is possible to obtain the same effects as those of the first embodiment with respect to the bonding between the copper member 2, the aluminum member 3A, and the intermediate layer 4. Furthermore, according to the present embodiment, since gaps are unlikely to occur between the copper member 2 and the intermediate layer 4 and between the intermediate layer 4 and the aluminum member 3A, it is possible to increase the thermal conductivity from the copper member 2 to the aluminum member 3A and improve the heat dissipation efficiency of the heat sink 30. Furthermore, the cutting fin forming process allows the multiple fins 32 to be easily formed.
[0060] [3. Third embodiment] [3-1. Copper-aluminum clad material] Next, a copper aluminum clad material and a manufacturing method thereof according to the third embodiment will be described. As shown in Fig. 6, the copper aluminum clad material 101 includes a copper member 102, an aluminum member 103, and an intermediate layer 104. The copper aluminum clad material 101 according to this embodiment differs from the first embodiment in that the intermediate layer 104 includes a plurality of continuous portions 105 and divided portions 106. The material types of the copper member 102 and the aluminum member 103 are the same as those of the first embodiment.
[0061] The intermediate layer 104 is a portion formed in a layered shape between the copper member 102 and the aluminum member 103. The intermediate layer 104 has a plurality of continuous portions 105 where the intermediate layer 104 is present, and a plurality of discontinuous portions 106 where the intermediate layer 104 is not present.
[0062] The intermediate layer 104 is formed of a metal material, for example, at least one metal selected from the group consisting of titanium, vanadium, chromium, manganese, cobalt, nickel, molybdenum, rhodium, palladium, silver, platinum, and gold, or an alloy thereof. The thickness of the intermediate layer 104 may be appropriately set, but is, for example, 10 μm or less, preferably 9 μm or less, more preferably 8 μm or less, even more preferably 7 μm or less, and particularly preferably 5 μm or less.
[0063] The intermediate layer 104 can be formed, for example, by subjecting the copper member 102 to a plating process, but may be formed by other methods. When the intermediate layer 104 is formed by a plating process, Ni electric plating, electroless Ni-P plating, Ni-Cr electric plating, or the like can be performed.
[0064] In the intermediate layer 104, the dividing portion 106 is a portion formed by dividing the intermediate layer 104. The size of the dividing portion 106 may be uniform, but in this embodiment, it is non-uniform. In addition, the interval between the adjacent dividing portions 106, 106 may also be uniform, but in this embodiment, it is non-uniform.
[0065] There is no oxide film between the copper member 102 and one surface of the continuous portion 105, and they are joined in an intimate contact state. In addition, there is no oxide film between the other surface of the continuous portion 105 and the aluminum member 103, and they are joined in an intimate contact state. More specifically, a new surface of the intermediate layer 104 formed by breaking the oxide film of the continuous portion 105 and a new surface formed by breaking the oxide film of the aluminum member 103 are joined in an intimate contact state by hot forging.
[0066] 7, the aluminum member 103 is densely inserted into each divided portion 106, and the copper member 102 and the aluminum member 103 are bonded in an intimate contact state without an oxide film being interposed between them. More specifically, a new surface of the copper member 102 exposed by the division of the intermediate layer 104 and a new surface formed by breaking down the oxide film of the aluminum member 103 are bonded in intimate contact by hot forging. The "intimate contact" in the claim "the new surface of the copper member exposed at the divided portion is bonded in intimate contact with the new surface of the aluminum member by flowing the aluminum member into the divided portion" is defined as above.
[0067] The ratio of the dividing portion 106 to the area of the interface between the copper member 102 and the aluminum member 103 is preferably 15 to 65%, more preferably 20 to 60%, and even more preferably 25 to 55%.
[0068] [3-2. Manufacturing method of copper-aluminum clad material] Next, a method for producing a copper-aluminum clad material according to the present embodiment will be described. In the method for producing a copper-aluminum clad material according to the present embodiment, a preparation step, a covering step, a lamination step, a heating step, and a forging step are performed in this order.
[0069] The preparation process to the heating process of this embodiment are generally the same as those of the first embodiment. As shown in Fig. 8, in the covering process, a covering layer 110 is formed over the entire periphery of the copper member 102. Although the method for forming the covering layer 110 is not particularly limited, in this embodiment, it is formed by a plating process.
[0070] As shown in Fig. 8, the forging process is a process in which the copper member 102 and the aluminum member 103 are pressed in a direction in which they approach each other with a predetermined pressure P to perform hot forging in the air (under the air atmosphere). The pressing time in the forging process may be set appropriately, but may be about 1 to 3 seconds, and is set to 1 second in this embodiment. The predetermined pressure P is preferably a pressure at which, when the forging process is performed, the coating layer 110 is divided, and the oxide film (not shown) of the coating layer 110 is removed to expose the new surface 110a, and the oxide film (not shown) of the aluminum member 103 is removed to expose the new surface 103a.
[0071] Moreover, the predetermined pressure P is preferably a pressure at which, when the forging process is performed, the coating layer 110 is divided to expose the newly formed surface 102a of the copper member 102, and the oxide film (not shown) of the aluminum member 103 is broken to expose the newly formed surface 103a. Moreover, the predetermined pressure P is preferably a pressure at which, when the forging process is performed, the oxide film of the continuous portion 105 of the coating layer 110 is broken to expose the newly formed surface 105a, and the oxide film (not shown) of the aluminum member 103 is broken to expose the newly formed surface 103a. The pressure P in the forging process according to this embodiment is equivalent to the pressure P described in the first embodiment.
[0072] In the forging process, the newly formed surface 105a of the continuous portion 105 exposed by the rupture of the oxide film comes into close contact with the newly formed surface 103a of the aluminum member 103, and is metal-bonded (diffusion-bonded). Furthermore, the newly formed surface 102a of the copper member 102 exposed by the rupture of the oxide film comes into close contact with the newly formed surface 103a of the aluminum member 103 exposed by the rupture of the oxide film, and is metal-bonded (diffusion-bonded). Since the coating layer 110 is formed by a plating process while removing the oxide film, in the forging process, the newly formed surface 102a of the copper member 102 exposed by the rupture of the coating layer 110 is free of the oxide film. Note that some of the overlapping reference numerals are omitted in FIG. 8.
[0073] The above steps form the copper-aluminum clad material 101. The presence or absence of the dividing portion 106 in the forging step is determined by changing each of the elements of the material and thickness of the coating layer 110 in the coating step, the temperature in the heating step, and the pressure in the forging step.
[0074] [3-3. Effects] The copper-aluminum clad material 101 and the manufacturing method of the copper-aluminum clad material according to this embodiment described above can achieve substantially the same effects as those of the first embodiment described above. That is, according to the copper-aluminum clad material 101 and the manufacturing method of the copper-aluminum clad material according to this embodiment, the coating layer 110 that suppresses the generation of oxides is provided on the copper member 102, and in the forging process, the newly formed surface 110a of the coating layer 110 and the newly formed surface 103a of the aluminum member 103 are bonded in close contact with each other while the copper member 102 and the coating layer 110 are in close contact with each other. More specifically, by pressing the heated copper member 102 and aluminum member 103 during the forging process, the oxide film of the continuous portion 105 of the coating layer 110 and the oxide film of the aluminum member 103 are destroyed, and the exposed newly formed surfaces 105a, 103a are bonded together. This makes it possible to suppress the generation of oxide between the copper member 102 and the coating layer 110 and between the aluminum member 103 and the coating layer 110, and makes it possible to form a copper-aluminum clad material 101 that is difficult to peel off.
[0075] Furthermore, by pressing the heated copper member 102 and aluminum member 103 during the forging process, the coating layer 110 is divided and the oxide film of the aluminum member 103 is destroyed, and the newly formed surfaces 102a, 103a exposed at the divided portion 106 are bonded together. This makes it possible to suppress the generation of oxide between the copper member 102 and the aluminum member 103, and to form a copper-aluminum clad material 101 that is difficult to peel off. In addition, since the aluminum member 103 is densely inserted into the divided portion 106, it is expected that the bonding strength can be increased by the anchor effect.
[0076] [4. Fourth embodiment] [4-1.Heat sink] Next, a heat sink and a manufacturing method of a heat sink according to a fourth embodiment will be described. As shown in Fig. 9, a heat sink 130 according to this embodiment includes a copper member 102, an aluminum member 103A, and an intermediate layer 104. The copper member 102 and the intermediate layer 104 (multiple continuous portions 105, divided portions 106) are the same as those in the third embodiment.
[0077] The aluminum member 103A includes a base 131 and a plurality of fins 132. The base 131 is a plate-shaped portion and is joined to the copper member 102 via an intermediate layer 104. The plurality of fins 132 are erected on the base 131 with gaps therebetween and are formed integrally with the base 131. There are no particular limitations on the method for forming the plurality of fins 132, and they can be formed, for example, by cutting.
[0078] [4-2. Heat sink manufacturing method] In the method for manufacturing a heat sink according to this embodiment, a preparation step, a covering step, a lamination step, a heating step, a forging step, and a fin forming step are performed in this order. The preparation step, covering step, lamination step, heating step, and forging step of the method for manufacturing a heat sink are the same as those of the method for manufacturing a copper aluminum clad material according to the third embodiment. In this embodiment, a cutting fin forming step in which fins are formed by cutting is performed as the fin forming step.
[0079] The cut fin forming process is a process of performing a cutting process on the aluminum member 103A of the copper-aluminum clad material to form a plurality of fins 132. In the cut fin forming process, for example, the plurality of fins 132 can be formed by cutting using a multi-cutter having a plurality of cutting teeth arranged in parallel.
[0080] [4-3. Effects] According to the heat sink and the manufacturing method of the heat sink according to the present embodiment described above, the same effects as those of the third embodiment can be achieved with respect to the bonding of the copper member 102, the aluminum member 103A, and the intermediate layer 104. That is, according to the present embodiment, gaps are unlikely to occur between the copper member 102 and the continuous portion 105, between the continuous portion 105 and the aluminum member 103A, and between the copper member 102 and the aluminum member 103A at the dividing portion 106, so that the thermal conductivity can be increased. Furthermore, the cutting fin forming step allows the multiple fins 132 to be easily formed.
[0081] [5.Other] <Modification of the coating process> In the above-described embodiment, the coating layer 10, 110 is formed by plating. The method of forming the coating layer 10, 110 is not limited thereto, and the coating layer 10, 110 may be formed by, for example, depositing, sputtering, casting-in, or the like a metal material on the copper member 2.
[0082] <Modification of the fin forming process> In the second and fourth embodiments, the case where the cutting fin forming process is performed as the fin forming process has been described as an example. The fin forming process may be a forging fin forming process in which fins are formed by forging.
[0083] The forged fin forming process is a process for forming a plurality of fins 32, 132 by deforming the aluminum member 3A, 103A of the copper-aluminum clad material by a cold, warm, or hot forging method.
[0084] The multiple fins 32, 132 may be formed by forging the aluminum members 3A, 103A in the forging process after the laminate 20 is forged and joined by hot forging in the forging process. That is, after joining by forging in the forging process, the fins may be formed by forging again in the forged fin forming process. Alternatively, the multiple fins 32, 132 may be formed by forging and joining the laminate 20 by hot forging in the forging process, and the multiple fins 32 may be formed by hot forging the aluminum members 3A, 103A in the forging process. That is, joining by forging in the forging process and fin formation by forging in the forged fin forming process may be performed simultaneously.
[0085] According to the heat sink and the method of manufacturing the heat sink according to the modified example of the fin forming step described above, the multiple fins 32, 132 can be easily formed by the forged fin forming step. EXAMPLES
[0086] [Test 1] In order to confirm the effect of the present invention, Test 1 was carried out. A test specimen was prepared, and a cross section was observed using a scanning electron microscope (SEM).
[0087] <Measurement of coating layer thickness> The thickness of the coating layer (plating layer) was obtained by measuring the film thickness at 10 arbitrary points on the coating layer contained in a cross-sectional SEM photograph taken with an SEM and calculating the average value of the 10 points.
[0088] <Porosity measurement> A cross-sectional SEM photograph was obtained by photographing the bonded interface at 1000 times magnification using an SEM. In the cross-sectional SEM image, the size (length) of the voids present at the interface was measured, and the total length in the interface direction was calculated. At this time, the size of each void was measured as the length of the longest part in the direction parallel to the interface. The percentage (%) obtained by dividing the total length of the voids by the total length of the bonded interface included in the field of view of the cross-sectional SEM photograph was taken as the porosity. Specifically, for the interface between the copper member and the continuous part of the intermediate layer, the porosity was calculated by dividing the total length of the voids present at this interface by the total length of the continuous part of the intermediate layer. In addition, for the interface between the continuous part of the intermediate layer and the aluminum member, the porosity was calculated by dividing the total length of the voids present at this interface by the total length of the continuous part of the intermediate layer. In addition, for the interface between the copper member and the aluminum member at the divided part of the intermediate layer, the porosity was calculated by dividing the total length of the voids present at this interface by the total length of the divided part of the intermediate layer.
[0089] <Condition> In Test 1, multiple copper aluminum clad materials 301 (301A to 301M) were prepared as test specimens, and the interfaces (bonding interfaces) were observed. As shown in Fig. 10, in Test 1, test specimens were prepared with different plating types and different thicknesses of the coating layer before forging, and each was observed. In terms of the "bonding results" in the rightmost column, in accordance with the definition of "adhesion" described above, those in which the porosity was less than 15% at any of the bonding interfaces were rated as "◯" (good), and those in which there was a bonding interface with a porosity of 15% or more were rated as "×" (poor).
[0090] In the manufacturing method of the copper aluminum clad material of Test 1, a preparation step, a covering step, a lamination step, a heating step, and a forging step are performed in this order. In the preparation step, a copper member JIS C1020 was prepared. The copper member was 100 mm long, 50 mm wide, and 3 mm thick. Also, an aluminum member JIS A6063 was prepared. The aluminum member 203 was 100 mm long, 50 mm wide, and 12 mm thick.
[0091] In the coating step, a plating process was performed to form a coating layer (finally an intermediate layer) on the entire surface of the copper member.
[0092] In the heating process, the copper and aluminum members on which the coating layer was formed were placed in a heating furnace, set to 500°C, and preheated in air for about 1 hour. In the forging process, the pressure was set to 600 (MPa) in an air atmosphere, and hot forging was performed for a pressure time of about 1 second. Through the above steps, test specimens were obtained.
[0093] In case 1 of test 1 (Examples 1 to 3, Comparative Example 1), electroless Ni-P plating was performed in the coating process. In each example, a coating layer having a thickness of 1.8 μm in Example 1, 3.9 μm in Example 2, 9.5 μm in Example 3, and 15.1 μm in Comparative Example 1 was formed.
[0094] In case 2 of test 1 (Examples 4 to 7, Comparative Example 2), electric Ni plating was performed in the coating step. In each example, a coating layer having a thickness of 4.7 μm in Example 4, 5.5 μm in Example 5, 7.4 μm in Example 6, 10.5 μm in Example 7, and 16.4 μm in Comparative Example 2 was formed.
[0095] In case 3 of test 3 (Example 8, Comparative Example 3, and Comparative Example 4), electric Ni-Cr plating was performed in the coating process. In each example, a coating layer having a thickness of 4.9 μm in Example 8, 5.9 μm in Comparative Example 3, and 6.5 μm in Comparative Example 4 was formed.
[0096] <Examples 1 to 3, Comparative Example 1> FIG. 11 is a scanning electron microscope photograph of Example 1. FIG. 11 is an SEM photograph taken at a magnification of 1000 times. In this specification, the SEM photographs with a scale bar of "10 μm" are SEM photographs taken at a magnification of 1000 times as in FIG. 11. As shown in FIG. 11, copper aluminum clad material 301A according to Example 1 includes copper member 302, aluminum member 303, and intermediate layer 304. Intermediate layer 304 has a plurality of continuous portions 305 and a plurality of divided portions 306. Copper aluminum clad material 301A has a coating layer (intermediate layer 304) having a thickness of 0.9 μm after forging. In Example 1, the interface between the copper member 302 and the continuous portion 305, the interface between the continuous portion 305 and the aluminum member 303, and the interface between the copper member 302 and the aluminum member 303 at the dividing portion 306 all had a porosity of less than 15% and were in close contact, and the joining results were good.
[0097] 12 is a scanning electron microscope photograph of Example 2. As shown in FIG. 12, the copper aluminum clad material 301B according to Example 2 includes a copper member 302, an aluminum member 303, and an intermediate layer 304. The intermediate layer 304 has a plurality of continuous portions 305 and a plurality of divided portions 306. The copper aluminum clad material 301B has a coating layer (intermediate layer 304) having a thickness of 2.7 μm after forging. In Example 2, the interface between the copper member 302 and the continuous portion 305, the interface between the continuous portion 305 and the aluminum member 303, and the interface between the copper member 302 and the aluminum member 303 at the divided portion 306 all had a porosity of less than 15% and were in close contact with each other, and the joining result was good.
[0098] FIG. 13 is a scanning electron microscope photograph of Example 3. As shown in FIG. 13, the copper aluminum clad material 301C according to Example 3 includes a copper member 302, an aluminum member 303, and an intermediate layer 304. The intermediate layer 304 has a plurality of continuous portions 305 and divided portions 306. The copper aluminum clad material 301C has a coating layer (intermediate layer 304) having a thickness of 7.9 μm after forging. In Example 3, the interface between the copper member 302 and the continuous portion 305, the interface between the continuous portion 305 and the aluminum member 303, and the interface between the copper member 302 and the aluminum member 303 at the divided portion 306 all had a porosity of less than 15% and were in close contact with each other, and the joining result was good.
[0099] FIG. 14 is a scanning electron microscope photograph of Comparative Example 1. FIG. 15 is an enlarged photograph of FIG. 14. As shown in FIG. 14 and FIG. 15, the copper aluminum clad material 301D according to Comparative Example 1 includes a copper member 302, an aluminum member 303, and an intermediate layer 304. The intermediate layer 304 has a plurality of continuous portions 305 and a plurality of divided portions 306. The copper aluminum clad material 301D has a coating layer (intermediate layer 304) having a thickness of 14.4 μm after forging. In Comparative Example 1, the porosity at the interface between the copper member 302 and the continuous portion 305 was 0%. However, voids Q were observed at the interface between the continuous portion 305 and the aluminum member 303, and at the interface between the copper member 302 and the aluminum member 303 at the divided portion 306. The porosity at the interface between the copper member 302 and the aluminum member 303 in the divided portion 306 was less than 15% and they were in close contact, but the porosity at the interface between the continuous portion 305 and the aluminum member 303 was 35%, and they were not in close contact, so the joining result was poor.
[0100] As described above, in case 1 of test 1 (Examples 1 to 3, Comparative Example 1), electroless Ni-P plating was performed in the coating process, and the bonding results were good when the thickness of the coating layer before forging was 1.8 to 9.5 μm, but defects occurred and the bonding results were poor when the thickness of the coating layer before forging was 15.1 μm. In other words, it is presumed that if the coating layer is too thick, it cannot follow the deformation of the copper member 302 and the aluminum member 303, and voids are formed at the interface. It was also found that the thickness of the intermediate layer (coating layer) becomes thinner than before forging by performing the forging process. It was also found that the thickness of the intermediate layer (coating layer) becomes thinner and the divided portion 306 is also formed by performing the forging process.
[0101] <Examples 4 to 7, Comparative Example 2> FIG. 16 is a scanning electron microscope photograph of Example 4. As shown in FIG. 16, the copper aluminum clad material 301E according to Example 4 includes a copper member 302, an aluminum member 303, and an intermediate layer 304. The intermediate layer 304 has a plurality of continuous portions 305 and a plurality of divided portions 306. The copper aluminum clad material 301E has a coating layer (intermediate layer 304) having a thickness of 1.9 μm after forging. In Example 4, the interface between the copper member 302 and the continuous portion 305, the interface between the continuous portion 305 and the aluminum member 303, and the interface between the copper member 302 and the aluminum member 303 at the divided portion 306 all had a porosity of less than 15% and were in close contact with each other, and the joining result was good.
[0102] FIG. 17 is a scanning electron microscope photograph of Example 5. As shown in FIG. 17, the copper aluminum clad material 301F according to Example 5 includes a copper member 302, an aluminum member 303, and an intermediate layer 304. The intermediate layer 304 has a plurality of continuous portions 305 and a plurality of divided portions 306. The copper aluminum clad material 301F has a coating layer (intermediate layer 304) having a thickness of 3.8 μm after forging. In Example 5, the interface between the copper member 302 and the continuous portion 305, the interface between the continuous portion 305 and the aluminum member 303, and the interface between the copper member 302 and the aluminum member 303 at the divided portion 306 all had a porosity of less than 15% and were in close contact with each other, and the joining result was good.
[0103] Fig. 18 is a scanning electron microscope photograph of Example 6. As shown in Fig. 18, copper aluminum clad material 301G according to Example 6 includes copper member 302, aluminum member 303, and intermediate layer 304. In Example 6, no divided portion is formed in intermediate layer 304. In copper aluminum clad material 301G, the thickness of the coating layer (intermediate layer 304) after forging is 3.9 µm. In Example 6, the porosity is less than 15% at the interface between copper member 302 and intermediate layer 304 and the interface between intermediate layer 304 and aluminum member 303, and the bonding results are good.
[0104] Fig. 19 is a scanning electron microscope photograph of Example 7. As shown in Fig. 19, the copper aluminum clad material 301H according to Example 7 includes a copper member 302, an aluminum member 303, and an intermediate layer 304. The intermediate layer 304 has a continuous portion 305 and a divided portion 306. The copper aluminum clad material 301H has a coating layer (intermediate layer 304) having a thickness of 8.4 µm after forging. In Example 7, the interface between the copper member 302 and the continuous portion 305, the interface between the continuous portion 305 and the aluminum member 303, and the interface between the copper member 302 and the aluminum member 303 at the divided portion 306 all had a porosity of less than 15% and were in close contact with each other, and the joining result was good.
[0105] FIG. 20 is a scanning electron microscope photograph of Comparative Example 2. FIG. 21 is an enlarged photograph of FIG. 20. As shown in FIG. 20 and FIG. 21, the copper aluminum clad material 301I according to Comparative Example 2 includes a copper member 302, an aluminum member 303, and an intermediate layer 304. The intermediate layer 304 has a plurality of continuous portions 305 and a plurality of divided portions 306. The copper aluminum clad material 301I has a coating layer (intermediate layer 304) having a thickness of 14.9 μm after forging. In Comparative Example 2, a plurality of voids Q were observed at the interface between the copper member 302 and the continuous portion 305, the interface between the continuous portion 305 and the aluminum member 303, and the interface between the copper member 302 and the aluminum member 303 at the divided portion 306. The porosity at the interface between the continuous portion 305 and the aluminum member 303, and the porosity at the interface between the copper member 302 and the aluminum member 303 in the dividing portion 306 were less than 15%, indicating adhesion, but the porosity at the interface between the copper member 302 and the continuous portion 305 was 21%, indicating no adhesion, and the joining result was poor.
[0106] As described above, in case 2 of test 1 (Examples 4 to 7, Comparative Example 2), when electric Ni plating was performed in the coating process and the thickness of the coating layer before forging was 4.7 to 10.5 μm, the bonding result was good, but when it was 16.4 μm, defects occurred and the bonding result was poor. In other words, if the thickness of the coating layer is too thick, it is presumed that the coating layer cannot follow the deformation of the copper member 302 and the aluminum member 303, and voids are formed at the interface. It was also found that the thickness of the intermediate layer (coating layer) becomes thinner than before forging by performing the forging process. It was also found that the thickness of the intermediate layer (coating layer) becomes thinner and the divided portion 306 is also formed by performing the forging process in Examples 4, 5, and 7. On the other hand, it was found that the thickness of the intermediate layer (coating layer) becomes thinner even when the forging process is performed in Example 6, but the divided portion is not formed. In other words, even if the divided portion is not formed in the intermediate layer as in Example 6, each interface can be bonded well.
[0107] <Example 8, Comparative Example 3, Comparative Example 4> FIG. 22 is a scanning electron microscope photograph of Example 8. As shown in FIG. 22, the copper aluminum clad material 301J according to Example 8 includes a copper member 302, an aluminum member 303, and an intermediate layer 304. The intermediate layer 304 has a plurality of continuous portions 305 and a plurality of divided portions 306. The copper aluminum clad material 301J has a coating layer (intermediate layer 304) having a thickness of 2.3 μm after forging. In Example 8, the interface between the copper member 302 and the continuous portion 305, the interface between the continuous portion 305 and the aluminum member 303, and the interface between the copper member 302 and the aluminum member 303 at the divided portion 306 all had a porosity of less than 15% and were in close contact with each other, and the joining result was good.
[0108] FIG. 23 is a scanning electron microscope photograph of Comparative Example 3. FIG. 24 is an enlarged photograph of FIG. 23. As shown in FIG. 23 and FIG. 24, the copper aluminum clad material 301K according to Comparative Example 3 includes a copper member 302, an aluminum member 303, and an intermediate layer 304. The intermediate layer 304 has a plurality of continuous portions 305 and a plurality of divided portions 306. The copper aluminum clad material 301K has a coating layer (intermediate layer 304) having a thickness of 3.9 μm after forging. In Comparative Example 3, a plurality of point-like voids Q were observed at the interface between the copper member 302 and the continuous portion 305, the interface between the continuous portion 305 and the aluminum member 303, and the interface between the copper member 302 and the aluminum member 303 at the divided portion 306. The porosity at the interface between the continuous portion 305 and the aluminum member 303, and the porosity at the interface between the copper member 302 and the aluminum member 303 in the dividing portion 306 were less than 15%, indicating adhesion, but the porosity at the interface between the copper member 302 and the continuous portion 305 was 26%, indicating no adhesion, and the joining result was poor.
[0109] FIG. 25 is a scanning electron microscope photograph of Comparative Example 4. FIG. 26 is an enlarged photograph of FIG. 25. As shown in FIG. 25 and FIG. 26, the copper aluminum clad material 301L according to Comparative Example 4 includes a copper member 302, an aluminum member 303, and an intermediate layer 304. The intermediate layer 304 has a plurality of continuous portions 305 and a plurality of divided portions 306. The copper aluminum clad material 301L has a coating layer (intermediate layer 304) having a thickness of 5.4 μm after forging. In Comparative Example 4, a plurality of point-like voids Q were observed at the interface between the copper member 302 and the continuous portion 305, the interface between the continuous portion 305 and the aluminum member 303, and the interface between the copper member 302 and the aluminum member 303 at the divided portion 306. The porosity at the interface between the continuous portion 305 and the aluminum member 303 and at the interface between the copper member 302 and the aluminum member 303 in the divided portion 306 was less than 15%, indicating good adhesion, but the porosity at the interface between the copper member 302 and the continuous portion 305 was 26%, indicating poor adhesion, and the joining result was poor.
[0110] As described above, in case 3 of test 1 (Example 8, Comparative Examples 3 and 4), electric Ni-Cr plating was performed in the coating process, and when the thickness of the coating layer before forging was 4.9 μm, the bonding result was good, but when it was 5.9 to 6.5 μm, defects occurred and the bonding result was poor. In other words, it is presumed that if the coating layer is too thick, the coating layer cannot follow the deformation of the copper member 302 and the aluminum member 303, and voids are formed at the interface. It was found that the thickness of the intermediate layer (coating layer) becomes thinner than before forging by performing the forging process. Also, in Example 8, it was found that the thickness of the intermediate layer (coating layer) becomes thinner and the divided part 306 is also formed by performing the forging process. [Explanation of symbols]
[0111] 1 Copper aluminum clad material 2 Copper materials 3. Aluminum components 3a New surface 4 Intervening layer 10 Covering layer 10a New surface 20 Laminate 30 Heat sink 31 Base 32 Finn 101 Copper aluminum clad material 102 Copper Materials 103 Aluminum components 103a New surface 104 Intervening layer 105 Continuous section 106 Divided part 110 Covering layer 110a New surface
Claims
1. A method for producing a copper-aluminum clad material by forging and joining a copper member made of copper or a copper alloy and an aluminum member made of aluminum or an aluminum alloy, comprising: the copper member has a coating layer formed of a metal material on a surface facing the aluminum member, the coating layer being in close contact with the surface of the copper member and capable of suppressing generation of oxides; a lamination step of laminating the copper member and the aluminum member in a state in which the coating layer and the aluminum member face each other to form a laminate; A forging process for hot forging the laminate to forge and join the laminate, In the forging process, a new surface of the coating layer and a new surface of the aluminum member are bonded to each other in a state where the copper member and the coating layer are in close contact with each other. A method for producing a copper-aluminum clad material.
2. In the forging step, the coating layer is divided to form a divided portion where the coating layer is not present between the divided coating layers, by flowing the aluminum member into the dividing portion, a new surface of the copper member exposed at the dividing portion and a new surface of the aluminum member are brought into close contact with each other, thereby bonding the copper member and the aluminum member. The method for producing the copper aluminum clad material according to claim 1 .
3. The metal material is at least one metal selected from the group consisting of titanium, vanadium, chromium, manganese, cobalt, nickel, molybdenum, rhodium, palladium, silver, platinum, and gold, or an alloy thereof; The method for producing the copper aluminum clad material according to claim 1 .
4. The coating step of forming the coating layer on the copper member is further included. The method for producing the copper aluminum clad material according to claim 1 .
5. The coating layer is a plating layer, In the covering step, the plating layer is formed by subjecting the copper member to a plating treatment. The method for producing the copper aluminum clad material according to claim 4.
6. The plating process is electric Ni plating, electroless Ni-P plating, or electric Ni-Cr plating; The method for producing the copper aluminum clad material according to claim 5.
7. The thickness of the plating layer is 15 μm or less. The method for producing the copper aluminum clad material according to claim 5.
8. The laminate further includes a heating step of preheating the laminate in an air atmosphere. In the former forging step, the laminate preheated in the heating step is hot forged in an air atmosphere. The method for producing the copper aluminum clad material according to claim 1 .
9. A method for manufacturing a heat sink, comprising the steps of: forming fins on an aluminum member while carrying out the method for manufacturing a copper aluminum clad material according to any one of claims 1 to 8; In the forging step, the laminate is hot forged to perform forging joining, and fins are formed on the aluminum member. A method for manufacturing a heat sink comprising the steps of:
10. After carrying out the method for producing a copper aluminum clad material according to any one of claims 1 to 8, A cutting fin forming process is provided for forming fins by subjecting the aluminum member to a cutting process. A method for manufacturing a heat sink comprising the steps of:
11. A copper-aluminum clad material in which a copper member made of copper or a copper alloy and an aluminum member made of aluminum or an aluminum alloy are joined together, The copper member and the aluminum member are joined with an intervening layer made of a metal material interposed between them, the copper member and the intermediate layer are in close contact with each other, and the intermediate layer and the aluminum member are in close contact with each other and joined together; The intermediate layer has a layer thickness of 10 μm or less. A copper-aluminum clad material comprising:
12. the intermediate layer has a continuous portion where the intermediate layer is present and a divided portion where the intermediate layer is not present, one surface of the continuous portion and the copper member are closely joined, and the other surface of the continuous portion and the aluminum member are closely joined, At the dividing portion, the copper member and the aluminum member exposed from the intermediate layer are bonded in close contact with each other. The copper aluminum clad material according to claim 11.
13. The metallic material includes nickel. The copper aluminum clad material according to claim 11.
14. A copper-aluminum clad material in which a copper member made of copper or a copper alloy and an aluminum member made of aluminum or an aluminum alloy are joined together, the aluminum member being provided with fins, said heat sink comprising: The copper member and the aluminum member are joined with an intervening layer made of a metal material interposed between them, the copper member and the intermediate layer are in close contact with each other, and the intermediate layer and the aluminum member are in close contact with each other and joined together; The intermediate layer has a layer thickness of 10 μm or less. A heat sink comprising:
Citation Information
Patent Citations
Heat sink and manufacture thereof
JP1997298259A